2015
DOI: 10.7324/japs.2015.50304
|View full text |Cite
|
Sign up to set email alerts
|

Clarias batrachus collagen extract increases fibroblast cell adhesion, migration and proliferation

Abstract: Collagen is an extracellular matrix protein with great importance in biomedical application. The search for collagen from various sources is intensified especially from marine source. This study was carried out to extract collagen from a Malaysian local fresh water fish, Clarias batrachus and characterized its biomedical potential In vitro. Collagen was extracted from C. batrachus skin using acetic acid method and identified using SDS-PAGE. MTT assay was performed to determine the effect of coated collagen on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…There are some disadvantages of these sources; for instance, forbidden usage due to religious restriction, and contamination of several transmitted diseases such as bovine spongiform encephalopathy (BSE) and transmissible spongiform encephalopathy (TSE), leading to a decrease in these use of collagen sources [26,33]. Therefore, marine collagen sources from fishes [34,35,36], sponges [37], squids [38], jellyfish [39], and others gain high interest due to no risk of transmitted diseases, their higher collagen content, low antigenicity, and a reduction in environmental waste [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some disadvantages of these sources; for instance, forbidden usage due to religious restriction, and contamination of several transmitted diseases such as bovine spongiform encephalopathy (BSE) and transmissible spongiform encephalopathy (TSE), leading to a decrease in these use of collagen sources [26,33]. Therefore, marine collagen sources from fishes [34,35,36], sponges [37], squids [38], jellyfish [39], and others gain high interest due to no risk of transmitted diseases, their higher collagen content, low antigenicity, and a reduction in environmental waste [33].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in traditional medicine and found to have multiple biological activities, such as anti-oxidant, anti-inflammatory, and anti-cancer activities [40,41]. Many studies have found that marine collagen extracts could increase cell proliferation and the migration of skin cells [35,36,42,43]. However, no research on the effects of abalone collagen on human keratinocytes has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Furthermore, some literature sources reported the suitability of African sharptooth catfish collagen in the acceleration of wound healing, and as a scaffold for tissue engineering. 39,40 The results of our research imply that collagen extracted from African sharptooth catfish and silver carp skins is biocompatible, in terms of ASCs growth, clonogenic potential, and differentiation in osteogenic and adipogenic lineages. Furthermore, fish collagen due to its anti-inflammatory and immune-modulatory properties, ability to stimulate cell adhesion, can improve wound resolution and closure, and has potential in bone and cartilage tissue engineering.…”
Section: Discussionmentioning
confidence: 79%
“…Although close to 28 proteins have been identified to belong to the collagen family, most of the collagens in the body are types I, II and III collagens [279]. Type I collagen is the most used collagen for coating silicone implants partly due to it being the dominant collagen within connective tissue and has been linked to enhanced fibroblast proliferation [281][282][283]. Being non-toxic as well as being biodegradable makes type I collagen a suitable material for coating silicone implant surfaces.…”
Section: Collagenmentioning
confidence: 99%